2018
DOI: 10.1371/journal.pone.0209154
|View full text |Cite|
|
Sign up to set email alerts
|

Extraversion personality, perceived health and activity participation among community-dwelling aging adults in Hong Kong

Abstract: Activity participation is essential to the wellbeing of aging adults. Divergent levels of activity participation within aging populations have been explained from diverse perspectives, but the interaction effects of key determinants, such as personality and health, are often ignored. This study examines the effects of extravert personality on aging adults’ activity levels by addressing its interaction with perceived physical health and mental health. A sample of 304 adults aged 50 and older was selected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Extraversion is one of the most critical personality traits, referred to as "sociability, activity, assertiveness, and positive emotionality", which means specific affection on participation in physical, cognition, and social activities (31). As confirmation for this finding, our study showed extraversion could be a predictor of mental HQL, physical HQL, and social relationship HQL, as well as death anxiety.…”
Section: Discussionsupporting
confidence: 78%
“…Extraversion is one of the most critical personality traits, referred to as "sociability, activity, assertiveness, and positive emotionality", which means specific affection on participation in physical, cognition, and social activities (31). As confirmation for this finding, our study showed extraversion could be a predictor of mental HQL, physical HQL, and social relationship HQL, as well as death anxiety.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, ter Bogt et al (2006) surveyed a sample of Dutch party-goers and found that there may be significant pre-drug differences between individuals who do and do not consume ecstasy across personality traits. Importantly, the individuals who consumed ecstasy were noted to have more extraverted personalities, a trait that has been linked to greater engagement in physical activity (Lai and Qin, 2018; Rhodes and Smith, 2006; Wilson and Dishman, 2015). Thus, pre-drug personality differences such as these may predict healthier lifestyles for individuals who consume ecstasy, leading to more positive physical health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in line with SET [ 13 ], older adults may need to exert even more effort to reduce or eliminate the age differences in performance. There is literature suggesting that older adults who are high in extraversion are more actively engaged both cognitive and physically with their environments than older adults low in extraversion [ 30 , 31 ] and rate themselves higher on self-efficacy [ 32 ]. If high extraversion older adults are highly engaged in and believe they have the capacity to succeed on difficult cognitive tasks like the n -back, then they may put forth more effort which would be commensurate with the higher levels of HR activation seen during the n -back compared to the BDS.…”
Section: Discussionmentioning
confidence: 99%